Sistema de contagem de fluxo de veículos - Bau Junior, Sergio Merlin (2016)
The traffic management is a growing problem due to increase in the volume of vehicles that travel on transport roads. The Pato Branco Department of Traffic (Depatran) has been counting the number of vehicles to plan its action to improve roads and implement appropriate traffic signalization, with the aim of ensuring security and user comfort. The counting is done manually, resulting in need of human counter to remain for several days and times in various parts of the city. The development of tools to carry out this activity avoids the exposure of the human counter to the outdoors with inadequate climatic states and provides a support mechanism for traffic management. This work presents the construction of a prototype to count the number of vehicles at a crossroads in urban traffic. The prototype has a circuit that uses an inductive sensor to detect vehicles and a program (to collect, process and present data) developed in an embedded system. For data visualization is used the user’s computer screen by USB communication with the embedded system. The prototype was tested in laboratory with steel and aluminum, and performed well.